GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 568768083 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false. The dataset includes 568768083 records from 12167 constituent datasets: 1669 records from Fungus herbarium, UiB. 76 records from BIRDRACE Nachtigallen. 79 records from BIRDRACE Blinde Hühner. 21447 records from Herbarium de Geo. B. Hinton, México. 188 records from Ökostation (Freiburg). 29 records from Klimaoasen in Köln. 116639 records from The digitization of plant specimens of NTU. 1 records from Red list project inventory, bryophytes. 19121 records from Biological Records Centre - Cerambycidae Dataset. 64 records from Schafheide im Böblinger Wald. 39 records from Regenrückhaltebecken Bad Bevensen. 10 records from Ökowerk Emden. 163011 records from Ichthyology Collection - Royal Ontario Museum. 64 records from Pilzlehrwald. 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 445 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 31879 records from Mollusca of Costa Rica (INBio). 220 records from Phthiraptera. 46530 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 2522 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 3633 records from Bioimages. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 48828 records from Grey seal at-sea distribution 2009-2014. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 2190 records from JOI - Herbário Joinvillea. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 10930 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 36867 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 23 records from AKG-Gelände in Bensheim. 53606 records from BioMar - LIFE project. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 15039 records from Northern Ireland Mammal Database. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 378 records from Tsetse flies of East Africa update. 8780 records from Artròpodes d'Andorra. 83 records from BIRDRACE Die Frankenpfeifer. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 1433 records from Naturalis Biodiversity Center (NL) - Crustacea. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 30366 records from Oregon State University Herpetological Collection. 8727 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 372 records from Otter survey of Ireland 2004 & 2005. 119 records from Bryozoa of the British Isles. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 129948 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 57210 records from National Biodiversity Data Bank. Observation records, 1900-2014. 10674 records from kpabg_lichens. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 2604 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 8220295 records from OEH Atlas of NSW Wildlife. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 218 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 27939 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 461 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 6 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 24454 records from Plan de vertebrados de la Patagonia. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 333 records from Macroarthropods, Isua 2013, Greenland. 206 records from The Diptera Site. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 459992 records from Royal Dutch Angling Association (SVN) - Piscaria. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 1 records from A new species of the genus Ectemnius Dahlbom, 1845 from Cameroon (Hymenoptera: Crabronidae). 1627 records from University of Calgary Herbarium. 3508 records from Entocytheridae (Ostracoda) World Database. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 8925540 records from Botanical Society of the British Isles - Vascular Plants Database. 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 85 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 111151 records from Jordal. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 998 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 8151 records from ISE - Herbário ISE. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 99133 records from Landesmuseum Kärnten. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 1484 records from IWDG Constant Effort Cetacean Sighting Scheme. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 8 records from Siphonaptera. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 6 records from Boimstorfer Sundern. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 7006 records from HUEM - Herbário da Universidade Estadual de Maringá. 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 9133 records from HUFU - Herbarium Uberlandense. 19 records from Revision von Suctobelba trigona (Michael, 1888). 13912 records from Fishes in MZNA-VERT: freshwater communities in the Larraun river (Spain). PhD project, Javier Oscoz & Master project, A. Cos.. 4107 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 179937 records from LACM Entomology Collection. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 155 records from A Review of the Jumping Spider Fauna (Araneae: Salticidae) of Chile. 172137 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 690 records from Mid Ulster Hare Surveys 2012-2015. 1 records from ISM Mammalogy Collection. 172498 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 50348 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 29644 records from Phanerogamic Botanical Collections (S). 10000 records from National Lesser Horseshoe Bat Database. 20 records from Truchas Mexicanas. 7034 records from Mollusca collection of National Museum of Nature and Science. 3 records from MSB Mammal Observations (Arctos). 190 records from Herpetofauna laguna El Tinije. 1236 records from Insect Collection (CeStuBio). 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 1 records from uconn-mammals. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 3204 records from Faunal Inventory of Morysin Nature Reserve. 1211 records from CCBER Herpetology Collection. 1 records from Karpfenteich, Klasse 6d. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 14379 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 58946 records from Biological Records Centre - Isopoda (Interim dataset). 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 114925 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 77 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 69799 records from African Rodentia. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 252137 records from MVZ Herp Collection (Arctos). 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 642 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 55785 records from PRECIS (KwaZulu-Natal Herbarium). 5709 records from Coleoptera of Piska Forest. 355 records from Herbier G. Garapin (BOUM). 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 10552 records from Biological Records Centre - Collembola Recording Scheme. 26534 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 1997 records from Aves de la cuenca media del río Bogotá. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3939 records from UFG - Herbário da Universidade Federal de Goiás. 4 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 1702 records from BioGIS - Bryophytes - HUJ collections. 212 records from Colección nacional de palmas de Colombia - JBQ. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 561 records from Herpetile collection, Natural History Museum, University of Oslo. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 56802 records from University of Vienna, Institute for Botany - Herbarium WU. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 9302 records from Ants from the Paraguayan dry Chaco. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 38567 records from Marine species distributions in Irish coastal waters. 5 records from Fledermäuse u. nachtaktive Insekten. 38541 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 4796 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 11 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 1150 records from Colección de Entomología - Diptera - Ceratopogonidae. 586 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 274 records from Bernhardsthal. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 10075 records from Nematoda of Costa Rica (INBio). 155194 records from Australian National Wildlife Collection provider for OZCAM. 89874 records from ecoscope_observation_database. 288 records from Fungi of Słowiński National Park, Poland. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 126 records from Schulwald Marksuhl. 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 2546 records from The atlas of butterflies in Kraków. 211789 records from MVZ Mammal Collection (Arctos). 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 2407 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 47667 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 13570 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 353 records from Coastal and marine species. 10250 records from Census of the flora of Benin. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 39321 records from Online Atlas of vascular plants 2012-2020. 4316 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 140273 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 1 records from Newly discovered sister lineage sheds light on early ant evolution. 60667 records from QLD DERM Coastal Bird Atlas (Trial). 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 5864 records from Herbarium Vonderau - FULD. 8784 records from Censo de aves acuáticas invernantes de la Comunidad Autónoma del País Vasco. 896 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 457499 records from Bird Atlas 2007 - 2011. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 6802 records from Tromsø Museum, Bryophytes. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 24 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1015 records from Irish Marine Turtle Database. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 33 records from New records in vascular plants alien to Kyrgyzstan. 574 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 9887 records from Orthopteroidea. 511 records from Coleoptera of Swierklaniec Forest. 45425 records from IAC - Herbário do Instituto Agronômico de Campinas. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 51277 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 547188 records from Bee Biology and Systematics Laboratory. 8300 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 3064 records from dec2011. 12234 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 557 records from Portuguese Seaweeds. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 6660 records from Weevils of the Tatra Mts.. 23048 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 5 records from Order Diptera, family Mydidae. 4730 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 2 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 25136 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 214 records from Collection of Heteroptera. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 4654 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 11 records from The larvae of Hydropsyche rhadamanthys Malicky 2001 and Hydropsyche sarpedon Malicky 2001 (Trichoptera: Hydropsychidae), endemics of Crete (South Aegean, Greece), with notes on their ecology. 3768 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 176729 records from CAS Entomology (ENT). 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 4671 records from Otter in coastal areas - Carcasses. 400 records from National Taiwan Ocean University. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 238 records from Irish Federation of Sea Anglers Catch Data. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 28772 records from EPA River Biologists data. 721 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 1254318 records from AntWeb. 295987 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 96 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 1 records from Lissotes working-group. 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 711 records from Colección Hidrobiológica del Chocó. 7250 records from All Ireland Marsh Fritillary Database. 670 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from New sighting of the endangered species blackchin guitarfish, Rhinobatos cemiculus, in the South Aegean Sea. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 5733 records from Small Mammal Research Database. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 224 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 8 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 2192 records from Zoology (Museum of Evolution - Uppsala). 423 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 2484 records from Marine Environmental Monitoring - Marine Turtles. 188 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 23608 records from CSIRO Ichthyology provider for OZCAM. 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 2 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 458 records from Herbarium Senckenbergianum (GLM) - Lichenes. 22451 records from TCWC Marine Invertebrates. 67 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 68 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 36411 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 24 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 2249 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 877374 records from Naturalis Biodiversity Center (NL) - Botany. 100 records from Brock University Herbarium (BU). 1 records from The larva and prepupa of Eupareophora exarmata (Thomson, 1871) (Hymenoptera, Tenthredinidae). 670416 records from PlutoF platform observations. 16774 records from KUBI Ornithology Tissue Collection. 10993 records from SPSF - Herbário Dom Bento José Pickel. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 6198 records from Plecoptera. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 890905 records from PRECIS. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 8581 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 1427 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 59522 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3503 records from CSIRO, Cruise SS200705, Benthic Biodiversity, Northwest Australia, 2007. 6425 records from Likona Invertebrates. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 1200 records from monocotyledonous_geophytes_of_fergana_valley. 3884 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 10135 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 24491 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 1157 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 541 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 9085 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 28172 records from Notes from the Mycology Herbarium, Oslo (O). 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 559142 records from Fishbase. 91719 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 7265 records from NHM, Heteroptera. 15 records from Projeto Abrace o Boto Cinza. 15996 records from UFP - Herbário UFP - Geraldo Mariz. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 190 records from Relative abundance of ostracods in sediment core Sv09. 106606 records from Occurrence records of southern African aquatic biodiversity. 1163 records from Paläontologie Marburg. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 2336 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 21 records from Hyolithen - SMF. 17618 records from BioGIS - Mammals - INPA database. 26998 records from SPF - Herbário da Universidade de São Paulo. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 139243 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 4967 records from SANT herbarium vascular plants collection. 9349 records from Harriet Irving Botanical Gardens (HIBG). 5 records from First records of Pseudodoros nigricollis Becker (Diptera: Syrphidae) from Cyprus. 174560 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 930 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 4432 records from Lepidoptera (Observations). 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 12808 records from WIWO (NL) - Migration of Pacific Golden Plovers through North-Eastern Mongolia. 353 records from Colección de Entomología - Arthropoda. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 269 records from BIRDRACE speedbirder. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 2 records from Collection Myriapoda - SNSD. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 165101 records from KUBI Mammalogy Collection. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 328 records from Insect Collection from New Caledonia. 9374 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 61 records from Registros restauración ecológica- Magdalena medio. 3176 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 558 records from Mammals in MZNA-VERT: skull and teeth development in Rattus and Mus. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 651 records from VMNH Invertebrate Paleontology. 2 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 3081 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2239160 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 1 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 451 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 10306 records from Cercle des mycologues de Montréal Fungarium (CMMF). 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 20662 records from ICN - Herbário do Instituto de Ciências Naturais. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 3257 records from fundiv france database. 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 76818 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 3083 records from Finnish Entomological Database: Heteroptera. 13 records from Perot Museum of Nature and Science. 4 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 47 records from Empria and Monsoma in Japan. 25970 records from NPL collections. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 654 records from Helgeland Museum, Tabanidae. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 883083 records from FLORIVON. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 1432 records from University of Amsterdam (NL) - Páramo pollen reference collection. 592367 records from Waarnemingen.be - Butterfly occurrences in Flanders and the Brussels Capital Region, Belgium. 47 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 1635 records from Mammal Recording Scheme, 1970-85. 3039 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 4027 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 16749 records from IMOS - AusCPR: Phytoplankton Abundance. 1605685 records from SA Flora (BDBSA). 9127 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 35762 records from Colección Herbario Federico Medem Bogotá - FMB. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 2011 records from Local BioBlitz Challenge 2013. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 4 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 381 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 2089 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 6139 records from HERBAM - Herbário da Amazônia Meridional. 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 111545 records from Highland Biological Recording Group - HBRG Insects Dataset. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 386575 records from Species data extracted from the National Vegetation Database. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 213 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 1157 records from API_CRSN_Data. 23366 records from Herbario Pontificia Universidad Javeriana. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 5079 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 2107 records from MLZ Mammal Collection (Arctos). 28363 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 7436 records from URM - Herbário Pe. Camille Torrand. 43882 records from University of Alberta Vascular Plant Herbarium (ALTA). 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 528 records from Collection Crustacea - KAUMM. 44 records from Solanum_baretiae. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 36971 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 500 records from Colección de Reptiles del Instituto Alexander von Humboldt. 71593 records from The avian collection at the Natural History Museum, Oslo, Norway. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 340766 records from Entomology, Natural History Museum, University of Oslo. 945 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 367 records from published_chenopodium_vulvaria_observations. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 30 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 534 records from Ascomycetes of Russian Fennoscandia. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 22641 records from IICT Herbário LISC. 81767 records from Herbario Universidad de Antioquia (HUA). 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 1093 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 628094 records from Inventario Español de Especies Terrestres (MAGRAMA). 751 records from Trichoptera (caddisflies) of Ireland. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 652 records from Spider species diversity from wet and dry habitats. 103104 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 338 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 61980 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 2240 records from Fongs d'Andorra. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 52 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 50453 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 231935 records from Lyman Entomological Museum (LEMQ). 6163 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 1 records from Herpetology. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 891 records from National Museum of Marine Biology and Aquarium. 3673137 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 9 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 89 records from BIRDRACE Uttenreuther Spatzenzähler. 10 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 615 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 10620 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 991 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 55897 records from AM: Freshwater Invertebrates (1900-2005). 1625 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 90 records from BIRDRACE TicTacToe. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 52 records from Isotope tracer experiment: meiofauna counts. 5053399 records from Southern African Bird Atlas Project. 2 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 5 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 11 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 194 records from Colección Herpetológica de la Patagonia. 19741 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 9037 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 9757 records from Collection of Coleoptera. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 63 records from (Data S1) Palynology of ODP Site 119-739. 678 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 7403 records from Fishes in MZNA-VERT: freshwater fishes of Hidalgo state (Mexico). 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 79407 records from NCSM Fishes Collection. 1359 records from Polychaetes from two subtidal rocky shores of the North coast of Crete, collected for the NaGISA project 2007-2008. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 129451 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 61002 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 1423 records from Reptilia notes, NTNU, Trondheim. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 721 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 11 records from Pollen profile from sediment core AV14_K2-4. 8865 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 918 records from Western Australia Museum, Crustacea Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1920-2004. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 4498 records from Colección Herbario Universidad Católica de Oriente. 36872 records from DMNS Bird Collection (Arctos). 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 61614 records from Atlas of Iberian water beetles (ESACIB database). 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 86088 records from NINA Vanndata øvrige arter. 3 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 100 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 33497 records from Dragonfly Ireland. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 23003 records from Amphibian Specimens. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 12247 records from ULg_Hexapoda. 2846 records from Coleoptera, NEF. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 4202 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 352872 records from BioFokus. 149215 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 1 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 2295 records from Joint Nature Conservation Committee - England Otter Survey Database. 34 records from Aschelminth collection of National Museum of Nature and Science. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 198 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2466 records from TTRS Ornithology. 372178 records from University of Florida Vertebrate Paleontology. 11826 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 236 records from GENT Lactarius Deliciosi. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 34 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 7204 records from Royal Horticultural Society - Records from the RHS insect reference collection. 133081 records from NINA insect database. 111020 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 355 records from Culture Collection of Cryophilic Algae. 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 1364 records from Irish Collembola records. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 34 records from Sipuncula collection of National Museum of Nature and Science. 25983 records from Monitoring data from the federal state Bavaria (Germany). 567 records from Collection of Hymenoptera. 2 records from Ichthyologie ZMK. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 767 records from BioGIS - Bats - Asaf Tsoar database. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 31 records from Fundación Miguel Lillo - Colección Invertebrados. 8399 records from UAM Fish Collection (Arctos). 78799 records from natagora-earlybirds. 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 401 records from The Fish Collection at the Zoologische Staatssammlung München. 582 records from Bioblitz 2013 Copenhagen Denmark. 80907 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 286822 records from Coordinated Waterbird Counts. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 68085 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 201 records from BioAcoustica: Wildlife Sounds Database. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 733 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 3688 records from Clare Biological Records Centre dataset. 880 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 9855 records from Bibliographic records of Angola mammals. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 97 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 588 records from Relative abundance of ostracods in sediment core Lz1120. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 6369 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 2222 records from CESJ - Herbário Leopoldo Krieger. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 2126 records from HAS-Algae - Coleção Ficológica do HAS. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 755 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 6080 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 393 records from Danish Lacewings (Neuroptera). 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 2 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 547 records from OUPR - Herbário "Professor José Badini". 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 22105 records from Global compendium of Aedes albopictus occurrence. 5 records from FCAB - Herbário Friburguense. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 1 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 1620 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 146 records from Megophthalmidia_of_North_America. 58 records from Mamíferos laguna El Tinije. 2356 records from MISE Project Otter Records, 2011-2015. 43 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 895 records from Lichen.ie Data. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 3372 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 1764 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 5095 records from HAMAB - Herbário Amapaense. 820426 records from Fauna Atlas N.T.. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 260 records from SuLaMa reptile survey II 2012. 58 records from LISU Herbario Angola. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 63 records from IWDG Ship Surveys Sightings - Heritage Council Surveys 2004. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 349121 records from Plantae of Costa Rica (INBio). 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 25887 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 7402 records from Helgeland Museum, Lepidoptera. 873 records from Kartlegging av spredning av fremmede bartrær. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 55 records from Molluscan fauna of Gueishan Island of Taiwan. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 41 records from CIM Specimens. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 10116 records from CUMV Mammal Collection (Arctos). 13200 records from CUMV Fish Collection (Arctos). 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 1839 records from Banc de Germoplasma Vegetal de les Illes Balears-JBS. 10254 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 27 records from HSU Wildlife Eggs and Nests. 136 records from Plants galls. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 690 records from Odonata collection, NTNU, Trondheim. 3842 records from CRCM Vertebrate Collection. 3 records from Diatom abundance of Hole 38-338, Part 2. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 12702 records from MBM - Herbário do Museu Botânico Municipal. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 4 records from A new pygmy grasshopper species (Tetrigidae: Tetriginae) from Central India. 2 records from CCBER Mammalogy Collection. 41565359 records from Artdata. 858 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 9686 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 461 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 8529 records from NINA botanical collection. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 75985 records from Irish Vascular Plant Data - Paul Green. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 3801039 records from FlorKart - FlorenKartierung Gefaesspflanzen. 53711 records from Field Museum of Natural History (Zoology) Bird Collection. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 24929 records from Tromsø Museum, Fungi. 109707 records from UAM Mammal Collection (Arctos). 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 7 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 51 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 2 records from Counts of benthos communities in Kongsfjorden in 2009. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 87 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 310 records from Lepidoptera collection, NTNU, Trondheim. 454 records from Collection des Mollusques (BOUM). 3 records from MfN - Micropaleontology. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 517579 records from Museum Victoria provider for OZCAM. 3947 records from The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forest.. 1742 records from Eggs Specimen. 21625 records from Butterflies of Ireland. 10902 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 1905 records from BioGIS - Reptiles - INPA database. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 99830 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 14371 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 7348 records from Herbier du Bénin. 9088 records from Flora of Słowiński National Park, Poland. 1960 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 1661 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 1335 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 35832 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 2 records from New genus of diminutive microhylid frogs from Papua New Guinea. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 14332 records from Cowan Tetrapod Collection - Mammals. 7416 records from The atlas of breeding birds in Małopolska. 71 records from (Data S1) Palynology of ODP Site 113-696. 759 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 763 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 7 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 314 records from Peces laguna El Tinije. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 612 records from INRA-Versailles Arabidopsis natural variants. 2282 records from Ohio University Invertebrate Paleontology Collection. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 2706 records from Alien macro-invertebrates in Flanders, Belgium. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 3884 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 1750 records from Flora of tanzania. 16192 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 78807 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 3020 records from Harvestmen_of_French_Guiana. 100757 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 238555 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 38282 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 20 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 2136 records from Herbario Museo de La Salle Bogotá (MLS). 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 6698 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 22680 records from Arctic Species Trend Index (ASTI) : Marine. 571178 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 221 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 2810 records from Helgeland Museum, Araneae. 4972 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 3275827 records from Insecta of Costa Rica (INBio). 3712 records from Saproxylic Beetles of Ireland. 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 18703 records from Endemic plants of the Congo basin. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 1662 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 20664 records from Arctic Species Trend Index (ASTI) : Terrestrial. 2 records from Description of Hoplolaimus bachlongviensis sp. n. (Nematoda: Hoplolaimidae) from banana soil in Vietnam. 10584 records from Danish Plant Bugs (Miridae). 28498 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 353 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 55002 records from Biological Records Centre - Reptiles and Amphibians Dataset. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" (1989-1996). 3217 records from Road Kill Survey. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 810 records from Chrysomelidae of the Carpathians. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 117 records from Various insect orders, NEF. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 27975 records from Inventaire National du Patrimoine Naturel : Loup en France. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 880841 records from SA Fauna (BDBSA). 3284 records from Algae (S). 71 records from HSU Wildlife Mammals. 411 records from SuLaMa reptile survey I 2012. 147466 records from AIMS, Long-Term Fish Visual Census, Great Barrier Reef, Northeast Australia, 1992-2015. 119 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 127937 records from OHN. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 431 records from Upper Silesian Museum, Insect Collection. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 27061 records from Bird Monitoring Data. 31962 records from Herbier de Nouvelle-Calédonie. 6 records from Malakologie ZMK. 13 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 158052 records from Field Museum of Natural History (Zoology) Mammal Collection. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 71220 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 199 records from MVZ Hildebrand Collection (Arctos). 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 51 records from Packer Collection / Xenochilicola bees, Chile. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 281 records from Myriapoda of Costa Rica (INBio). 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 1 records from Ornithologie ZMK. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 9893 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 13488 records from Lund Museum of Zoology (MZLU). 167094 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 2 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 495749 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 107 records from Landschaftsschutzgebiet Buchhorst 3. 633712 records from Données ONF Faune-Flore-Fonge. 1 records from Vermes ZMK. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 1 records from Reptilia ZMK. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 283 records from Crustacea ZMK. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 1523 records from Colección de Zoología Invertebrados - Otros invertebrados. 4 records from Culture Collection of Algae. 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 72596 records from CAS Invertebrate Zoology (IZ). 10 records from Description of a new species of the genus Chaetostoma from the Orinoco River drainage with comments on Chaetostoma milesi Fowler, 1941 (Siluriformes: Loricariidae). 4240 records from Crustacea collection of National Museum of Nature and Science. 2 records from Echinodermata ZMK. 3512 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 2 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 6516 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 9 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 965 records from Freshwater plants of Cameroon. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 396127 records from British Lichen Society - BLS Lichen Database: English churchyards. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 60 records from Shrews of Poland. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 19084 records from UAM Bird Collection (Arctos). 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 3406 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 2952 records from Geneva Herbarium – Burnat Herbarium (G-BU). 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 9015 records from Tallinn Botanic Garden. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 278 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 614 records from UCM Bird Eggs/Nests Collection (Arctos). 8395 records from Herbarium areqvipense (HUSA). 440 records from NCSM Birds Collection. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 3620 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 2070 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 200 records from Zoological collection of the National Museum. 2742 records from Plant (KIWE-PL). 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 5561 records from IWDG Casual Cetacean Sightings. 1000 records from Colección Limnológica del Chocó. 749207 records from Historical Bird Atlas. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1025 records from tef-database. 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 688 records from Algae, Norwegian College of Fishery Science. 15866 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 144 records from Annelida collection of National Museum of Nature and Science. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 59 records from CCBER Ornithology Collection. 1151 records from arim. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 1051449 records from Norwegian Biodiversity Information Centre - Other datasets. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 122 records from Stever. 8717 records from CHAS Mammalogy Collection (Arctos). 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 19695 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 2080 records from Naturalis National Natural History Museum (NL) – Coelenterata. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 240 records from MPM Herpetology. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 291693 records from SEAPOP NINA. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 7551382 records from BirdLife Australia, Birdata. 102 records from BIRDRACE Niederrheinische Bartgeier. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 7 records from (Table 4) New palynological record of sediments from Odderade. 4440 records from Invertebrate collection of University of Oulu Zoological Museum. 5108 records from ESAS cetacean sightings from 1980 to 2003.. 750647 records from Museum of Comparative Zoology, Harvard University. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 1406 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 35266 records from Kathryn Kalmbach Herbarium. 3375 records from NMMNH Mammal. 12 records from Naturalis Biodiversity Center (NL) - Mammalia. 686 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 9192 records from Herbarium of the Université Libre de Bruxelles. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 15 records from Tardigrada collection of National Museum of Nature and Science. 10502 records from Naturalis Biodiversity Center (NL) - Cnidaria. 4905390 records from Australia's Virtual Herbarium. 5 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 13315 records from Collection of various insect orders, Natural History Museum, University of Oslo. 431 records from Plantas Bosque Seco Chicamocha. 9948 records from Bees of Canada / Gschwendtner property collection. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 51474 records from Vascular Plant Herbarium, UiB. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 1299 records from Waarneming.nl (NL) - Great Grey Shrike Count 2014-2015. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 589 records from Birds (NMNO-BI). 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 1657161 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 443 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 697 records from Herbier de Strasbourg. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 56431 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 17 records from Hazel Dormouse in Ireland. 35480 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 163 records from Entomofauna laguna El Tinije. 65529 records from CAS Ornithology (ORN). 210866333 records from EOD - eBird Observation Dataset. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 169 records from The Pteridaceae family diversity in Togo. 46685 records from Tasmanian Museum and Art Gallery provider for OZCAM. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 1098 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 37 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 1571 records from Banco de Germoplasma del Jardín Botánico Atlántico. 118931 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 259723 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 161 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 1380439 records from Consortium of California Herbaria. 110 records from BIRDRACE Linumer Luchschleicher. 1294 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 27033 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 65 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 21868 records from Fishes in MZNA-VERT: foraging ecology of the kingfisher. PhD project, Antonio Vilches. 561 records from Líquens d'Andorra. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 74 records from SuLaMa reptile monitoring. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 135609 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 6004 records from Colección Limnológica Universidad de Antioquia. 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 4817324 records from Bird Ringing Centre in Sweden (NRM). 796 records from Biological Records Centre - Irish Otter Dataset. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 1 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 8407 records from NYSM Birds. 5311 records from Natural History Museum Maastricht (NL) - Herbarium. 16504 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 49637 records from Monitoring data from the federal state Hesse (Germany). 8014 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 3002 records from Colección de Peces Universidad Católica de Oriente. 1458 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 2262 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 156129 records from CONN. 914 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 3564 records from HUCS - Herbário da Universidade de Caxias do Sul. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 56 records from UCM Vertebrate Observations Collection (Arctos). 3214 records from Upper Silesian Museum, Bird Observations. 13720 records from Hemipteran specimens of Iwate Prefectural Museum. 2 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 11615 records from Louisiana State University Herbarium - Vascular Plants. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 2 records from Neue Milbenarten aus Kärnten. 14122 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 3669 records from ARKO strandeng. 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 33173 records from Global Lacustrine Diatoms. 662 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 1019825 records from iNaturalist Research-grade Observations. 5506 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 9741 records from Finnish Entomological Database: Hymenoptera. 62 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 790 records from UCBG TAPIR Provider. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 34 records from National System of Protected Areas in Poland - Fungi. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 16246 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 7470 records from National Taiwan University. 5790 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 5 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 1589 records from Global caridean shrimp fauna. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 40458 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 202161 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 3225 records from Aquatic Oligochaeta of Ireland. 2 records from A new species of Neossos Malloch (Diptera: Heleomyzidae) from the Yukon Territory, Canada, and a revised key to the Nearctic species. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 20893 records from H.A. Stephens Herbarium. 3 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 23 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 40132 records from Recent Invertebrates Specimens. 32 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 3592 records from Coleção de Polychaeta do Museu Nacional. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 41 records from Shieldbug Records. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 557841 records from Aranzadi Ringing Scheme (bird ring-recovery data). 1077 records from BioGIS - Fish - HUJ collections. 46 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from A new ant genus from the southwestern United States.. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 70416 records from National Bat Database of Ireland. 65 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 19 records from Flora of Japan Specimen Database. 6309 records from University of Lethbridge Herbarium (LEA). 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 45761 records from Estonian Museum of Natural History. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 50000 records from observe_tuna_bycatch_ecoscope. 10862 records from Heteroptera of Ireland. 2201 records from UFRN-Fungos - Herbário UFRN - Fungos. 43 records from A Unique Nest-Protection Strategy in a New Species of Spider Wasp. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 1894 records from Fungi Collection. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 13701 records from AM: Terrestrial Insect Collections (1896-2000). 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 71 records from Spiders_of_French_Guiana. 2877 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 31 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 6823 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 103322 records from Invertebrates Collection of the Swedish Museum of Natural History. 9636 records from KUBI Ichthyology Tissue Collection. 181 records from Alien Species in Poland - Animals. 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 11 records from Pollen profile from sediment core AV14_K2-1. 1020 records from National Museum Of Marine Science & Technology. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 3330 records from Collection botanique Le Grand A. (BOUM). 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 1321 records from Herbier National de Mauritanie (HNM). 5 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 86277 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 69 records from Schulgarten mit Klasse 8a (Essen). 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 17944 records from University of California Museum of Paleontology. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 2752 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 471 records from DMNS Marine Invertebrate Collection (Arctos). 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 2121 records from HUSC - Herbário Unisanta. 21 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 189 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 2775 records from Bolivian Amazon lowland fish metacommunity data. 3 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 419508 records from Meadow and Pasture Inventory (SJV). 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 84521 records from BioGIS - Vascular plants - INPA database. 9491 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 1244 records from Mosquitoes_of_French_Guiana. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 66072 records from ALCB - Herbário Alexandre Leal Costa. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 1359 records from CSIRO, Cruise SS199701, Marine Biological Survey, South Tasmania, Southeast Australia, 1997. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 1001 records from Circumpolar Seabird Monitoring Plan. 38535 records from Mammals housed at MHNG, Geneva. 1443 records from Odonata of the Congo River 2010 expedition. 9600 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 56 records from Onychophora of Costa Rica (INBio). 23215 records from rmca-albertine-rift-butterflies. 14540 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 104356 records from mel. 8441 records from Natural England - Batsites inventory for England. 178290 records from Essig Museum of Entomology. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 257 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 3628 records from Wildbook for Whale Sharks. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 613 records from Countryside Council for Wales - Shad Monitoring data. 1116 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 39766 records from BioGIS - Vascular plants - A. Danin's point database. 17435 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 1340 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 1658 records from MISE Project Waterford Otter Records, 2011-2015. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 22029 records from TNHC Ichthyology Collection. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 84 records from Roter Berg Werdau (Leubnitz). 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 13298 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 40 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 14072 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 15926 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 8052 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 3 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 1189 records from kerkyra. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 1474 records from Herbarium Rhoenmuseum Fladungen. 118754 records from Estonian University of Life Sciences. 23128 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 172719 records from CAS Ichthyology (ICH). 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 34 records from Order Araneae. 10 records from Redescription of the little-known grasshopper Willemsella (Acrididae, Hemiacridinae) from Peninsular Malaysia. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 3327 records from BioGIS - Mammals - SPNI. 18 records from Landschaftsschutzgebiet Buchhorst2. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 2 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 1682701 records from NMNH occurrence DwC-A. 15219 records from Census of the animals of Benin. 68 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 1826 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 12857 records from DMNS Mammal Collection (Arctos). 22029 records from Fishes in MZNA-VERT: baseline freshwater sampling campaigns. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 24211 records from Monitoring data from the federal state Saxony (Germany). 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 251760 records from Moths Ireland. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 128741 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 20 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 13624 records from Mammal collection, Natural History Museum, University of Oslo. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 128 records from Birdrace-Brut-Wetteraukreis. 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 1294 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 112 records from Birdrace_Die_Borner-Viersen. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 96 records from Birdrace-federleser-Herford. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 108 records from Birdrace-TriumVIErat-Viersen. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 100 records from Birdrace-Meister_der_Herzen-Kleve. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 95 records from Birdrace-Buteo1_DO-Dortmund. 120 records from Birdrace-Kosmos_Racer-Freising. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 18353 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 114 records from Birdrace-Finkenspötter-München. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 109 records from Birdrace-Team_Charadrius-Günzburg. 105 records from Birdrace-ARKONAuten-Rügen. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 101 records from Birdrace-Herford-Birder-Herford. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 92 records from Birdrace-Team_BO-bachter-Bochum. 91 records from Birdrace-Enger_am_Spektiv-Herford. 85 records from Birdrace-Die_Paradiesvögel-Herford. 127 records from Birdrace_Schräge_Vögel-Herford. 103 records from Birdrace-Die_Nachtigallen-Herford. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 59 records from Im Bauerngarten. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 746 records from Literature based species occurrence data of birds of North-East India. 111 records from Birdrace-Uhulogen-Lippe. 110 records from Birdrace-LiLaMai-Vechta. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 137 records from VFD-H: Rheingau: Pferdeweide Loock. 342 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 100 records from Feriendorf Ober-Seemen. 80 records from Förderzentrum Schmölln. 70 records from Lech 2001. 101 records from Naturgrundstück (Eutin). 97 records from Döchtbühlwald (Bad Waldsee). 15 records from AKG-Bensheim. 263 records from Artenvielfalt Kreis Gießen. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 45 records from Flusswerder in der Weser (Hameln). 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 86 records from Alter Kreidebruch Saßnitz/Rügen. 72 records from Birdrace-Buteo2DO-Dortmund. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 76 records from Birdrace-Birding_for_Nature-Bonn. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 88 records from Birdrace-WeserEggeLäufer-Höxter. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 185 records from Klasse 3a. 151 records from Isarufer. 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 57 records from Waldhusener Moor (Lübeck-Kücknitz). 233 records from Föhrenried (Fronreute und Baindt). 270 records from Regenrückhaltebecken (Zeulenroda). 282 records from Deponie Klausdorf. 313 records from Stadtpark Herzberg (Elster). 170 records from Bodenseeufer Radolfzell. 56 records from Zitadelle Berlin-Spandau (7b). 54 records from Wiese am Unterbecken. 95 records from Ortelsbruch - Hangmoor bei Morbach. 41 records from Örtzemündung (Stedden). 101 records from Naturhausgarten. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 241 records from BIRDRACE RennVögel Münsterland. 162 records from Siegen/ Gymnasium Am Löhrtor. 34 records from Borkhart. 360 records from Küstenschutzwald. 198 records from FNL e.V.. 342 records from Kremmer Luch. 271 records from Beweidungsprojekt an der Nesse. 114 records from Flora. 122 records from Kloster Eberbach. 97 records from LauWi. 144 records from Ehmkendorf. 52 records from Fledermaus. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 87 records from Biotop "Kohlbeke" (Berlin-Marzahn). 57 records from Heidesee / Halle. 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 257 records from Seewasen. 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 83 records from Spechtwald. 50274 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 100 records from Grenzturm Hohen Neuendorf. 55 records from Waldsee. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 113 records from Hochschulgelände (Bremen). 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 29 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 37 records from Berlin - Treptower Park / Karpfenteich. 44 records from "Schlechteberg" Ebersbach/Sa.. 69 records from Lassentiner Moor (Niepars). 245 records from Kiesgruben Wemb. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 23 records from Alter Nördlicher Friedhof (München). 20 records from Motzener Tonsee. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 150 records from Steinbruch Mainz-Weisenau. 22 records from Dellwiger Bach (Dortmund). 69 records from "Schwarzes Teich" (Waldpark Radebeul). 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 167 records from Zielbach (Töll). 39 records from Südpark (Bochum-Wattenscheid). 66 records from Wedeler Au. 64 records from Kabelskebach (Kabelsketal, Saalkreis). 158 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 325 records from Triebesbach (Zeulenroda-Triebes). 6223 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 46 records from Hainbachtal in Oelsnitz/V.. 308 records from Wangerooge. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 219 records from Umgebung der Grundschule Oderberg. 96 records from Die Wuhle. 58488 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 149 records from Wirbach. 253 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 113 records from Rund um das LUGY. 50 records from Junge Heide, Radebeul/Dresden. 85 records from Insektenvielfalt Ahe/Weichelsee. 161 records from Schussenaue bei Berg. 31 records from Nationalpark Harz Schul-AG Braunlage. 106 records from Schulgarten Hans-Carossa-Oberschule. 18 records from Spielwiese. 12 records from Kindergarten. 79 records from GymnQuerfurt. 63 records from Erft in Selikum (Neuss). 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 73 records from Varnhalt. 163 records from Brander Wald (Stolberg). 79 records from Balkon (Norderstedt). 103 records from Wasserwerkspark (Chemnitz). 111 records from Ökologischer Weinberg (Guntersblum). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 35 records from Urwald 3 (Bad Waldsee). 77 records from Trockenrasen Franzigmark (Halle/Saale). 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 180 records from Paul-Gerhardt-Schule Dassel. 145 records from privater Garten. 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 54 records from Ludwigshofen. 108 records from Mainufer. 32 records from Schulhof Sandhofenschule (Mannheim). 124 records from Wiesenbiotop am Wasserturm. 1035 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 41 records from Wiese und Bach beim Unterbecken (Markersbach). 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 110 records from Obstwiese Osterberg. 4 records from Schulbiotop und Brigach (Villingen). 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 28 records from Hainbachtal bei Oelsnitz / V.. 55 records from Flora und Fauna am Mittelrheintal. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 60 records from Schafsweide Seniorenhaus Berghof. 95 records from Vielfalt verschiedener Wiesen. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 101 records from Isartal Dingolfing. 103 records from Schwanseepark (87645 Schwangau). 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 245 records from Gieselbachtal Fulda-Harmerz. 214 records from Binsenwiesen. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 147 records from NABU-Auerochsenweide. 92 records from Birkenloh. 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 97 records from Landschaftspark St.Leonhard-Deisendorf. 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 71 records from Bolzplatz. 117 records from Wassermann. 9 records from Willersalpe. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 54 records from Zentralfriedhof (Wien). 18 records from Mittelstreifen. 59 records from Rund ums Ökohaus (Würzburg). 181 records from Spießwoogtal / Königsbruch (Fischbach). 212 records from Artenvielfalt im Beckerbruch (Dessau). 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 99 records from Düne am Ulvenberg (Darmstadt). 28 records from Sandgrube Zaisertshofen. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 160 records from Wirbach-Taubental (Bad Blankenburg). 48 records from Trockenrasen bei Dörndorf. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 99 records from Dorfrand Mauderode. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 16479 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 59 records from Oschenberg, NO von Bayreuth-Laineck. 98 records from Warnowtal (Rostock). 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 19 records from Goethe-Hauptschule/Projekt I-10. 153 records from Selztal bei Friesenheim. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 22 records from Breitkopfbecken (Berlin-Reinickendorf). 139 records from NSG Leist bei Ziegenhain. 40 records from Flächennaturdenkmal Grubditz. 62 records from Amtsrain Apolda-Zottelstedt. 43 records from Saalewiesen Naumburg. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 43 records from Schulgelände Thurmair-Gymnasium. 65 records from Mauernacker (Wettsaasen). 5 records from Streuobstwiese (Mittelgasse 4). 17 records from Schutzgebiet Ochtersum. 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 11 records from Desarrollar las actividades tendientes al manejo, conocimiento y conservación del Comino crespo (Aniba perutilis hemsl.), formuladas en el plan de conservación para la especie en el departamento del Meta. 22 records from Heilpflanzen im Hainbachtal. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 50 records from Artensuche auf den Elbwiesen in Radebeul. 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 28 records from Uferzone Wipper (Biesenrode). 61 records from Artenvielfalt auf der Wiese. 81 records from Stadtpark Schmölln. 244 records from WildesMoor bei Schwabstedt. 53 records from Weidegut Rechab. 155 records from Bammentaler Duft- und Heilkräutergarten. 748 records from Moluscos Marinhos de Augusto Nobre. 94 records from Kochertgraben II. 172 records from Dalbekschlucht. 93 records from Höltigbaum. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 63 records from Hochschule Zittau/Görlitz. 98 records from Rund ums Cani. 107 records from vegoek. 46 records from Neanderthal. 86 records from Naturerlebnisraum Koppelsberg (Plön). 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 60 records from NABUGEO1. 109 records from ZFMK AMIBIO. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 58 records from Weidewirtschaft. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 61 records from GE-Brühl. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 207 records from Biosphäre Bliesgau. 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 69 records from Entdeckertour am Muldestausee 1/05. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 155 records from Birdrace-Usedommeln-Ostvorpommern. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 128 records from Birdrace_turbine_untersee-Konstanz. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 15 records from Regenwasserabfangsbecken (Erlenbach). 193 records from Gelände des Schulzentrums am Himmelsbarg. 9866 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 39 records from Soolbach-Tal. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 102 records from Industriebrache (Kempen). 4 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 36 records from Selz (Ingelheim am Rhein). 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 142 records from Kinderbauernhof Pinke-Panke. 39 records from Stausee Weiditz. 65 records from LSG "Großes Bruch". 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 355 records from Carábidos (Coleoptera: Carabidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 10 records from Feuchtwiesen Wippertal bei Wippra. 54 records from Weidegebiete in der Selzrenaturierung. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 134 records from Birdrace-Team_Havelland-Havelland. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 5 records from Naturschutzgebiet Ahrmündung (Remagen). 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 100 records from Birdrace-The_Ringers-Friesland. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 2913 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 89 records from Birdrace-Team_Wangerooge-Friesland. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 53 records from Bad Bodenteicher Heide. 57 records from Garten in Schmölln. 172 records from Leben im Finkensteiner Moor. 133 records from Wulfsmuehle/Pinnau. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 122 records from Birdrace-Hügelland-Mainz/Bingen. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 79 records from Birdrace-Bielefinken-Bielefeld. 42 records from sbosch. 23 records from Wiese Niederaula. 13 records from Garten Hamburg Uhlenhorst. 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 41 records from Morphologische Daten von Natrix. 46 records from 8c. 221 records from Römertal (Steinpleis). 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 81 records from Birdrace-Die_Ornithomaten-Herford. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 78 records from Birdrace-Die_Laufenten-Braunschweig. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 21 records from Tauchen und Meer 02. 35 records from Gym Freyung. 64 records from Issumer Fleuth. 27 records from Zwickau- Schwanenteich. 1174 records from Sudeniederung (Amt Neuhaus). 27 records from Wiese hinter der Schule (Darmstadt). 29 records from Insekten. 611 records from IBF Monitoring of Plant Galls. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 62 records from Zoo Frankfurt. 31 records from Kurler Busch (Scharnhorst). 57 records from Schulgarten Fichteschule. 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 21 records from Bach. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 31773 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 63 records from Sternwiese Mülheim-Broich. 21 records from Riedkanal Bötzingen. 71 records from Birdrace-do_elster_Dortmund. 29 records from Naturerfahrung. 87 records from Klütwald. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 36 records from Plöwener Wald. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 51 records from Steinbachtal (Würzburg). 54 records from Park Schönfeld (Kassel). 40 records from Schulhof Liebfrauenschule Oldenburg. 51 records from Schrebergarten Düsseldorf Oberkassel. 49 records from Dörnberg. 47 records from Schulgelände Ceciliengymnasium. 22 records from Bachabschnitt der Nette (Osnabrück). 81 records from Schulgarten-St.-Georg-Gymnasium. 8 records from Streuobstwiese. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 31 records from Regenwasserabfangbecken. 4334 records from MVZ Bird Observations (Arctos). 84 records from Streuobstwiese Haus Zeitz. 26 records from Erhard Sopp. 27 records from Vögel. 101 records from Hoher Stein Kallenhardt. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 141 records from Draubiotop Lavamünd. 11 records from Waldgebiet Todtnau- Sonnhalde. 57 records from Mauervegetation,Flechten und anderes. 117 records from Naturschutzgebiet Kochertgraben. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 51 records from Mühlenbach bei Buxtehude. 13 records from Tiere im Teichgebiet. 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 56 records from Estetal (Buxtehude). 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 26 records from Schulteich Heinrich-Mann-Schule. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 32 records from Nationalpark Harz Juniorranger. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 29 records from Brenz (Heidenheim). 19 records from Glemstal (Leonberg). 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 36 records from Olympiapark (München). 20 records from Lerchenauer Baggersee (München). 24 records from Ornithologische Wanderung um Tussenhausen. 28 records from Stadtpark Prinzengarten (Sigmaringen). 24 records from Kaisertal. 48 records from Heider Bergsee (Brühl). 15 records from Beisetal bei Niederbeisheim. 29 records from Schulaktion des Dienzenhofer-Gymnasiums. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 23 records from Ackerrain Plönhagen. 10 records from schlittschuhweiher. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 12 records from Kinderwald Hannover. 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 36 records from Salzwiese Diekskiel. 3 records from FFR Hausen. 45 records from Georgs-Padd (Wangerooge). 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 9 records from Wiesendreieck Luckenwalde. 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 18 records from Schulgarten der Gesamtschule Am Heidberg. 80 records from Lahnufer in Villmar. 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 8 records from Kleiner Ziergarten Winzingen (Neustadt). 22 records from Kaltenkirchen Brache. 20 records from Mikroorganismen. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 15 records from Bodentiere rund um die Schule. 16 records from Im und um das Schulhaus. 5 records from Feuchtwiese. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 11 records from Privatteich(St.Leon). 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 15 records from Kirchheller Heide ( Bottrop). 10 records from Bachpatenschaft Beeke. 15 records from Urwald 2 (Bad Waldsee). 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 23 records from Tümpel Schulbiologiezentrum. 13 records from FND "Weißer Berg" Leißling. 6 records from Fließgewässeruntersuchung am Haselbach. 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 13 records from Warnowufer Groß Klein. 8 records from Krittenhorster Wald (Ostkilver). 21 records from LBV-Kindergruppen Markt Tussenhausen. 23 records from Wattuntersuchung (Cuxhaven). 34 records from Wattenmeer-Safari (Wurster Watt). 17 records from Tierpark Zittau. 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 1 records from Graureiher in Lans. 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 6 records from Sächsische Schweiz (Pfaffenstein). 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 40 records from Tiere und Pflanzen um uns herum !. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 24 records from Tauchen und Meer. 18 records from Naturtag. 15 records from Tiere. 59 records from Schulteich Freie Waldorfschule Darmstadt. 7 records from Stadtrandlandschaft Apolda-Nord. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 135 records from Waldi-Weiher. 1 records from Haslauer Moor. 2 records from Hildener Heide - Spörkelnbruch (Haan). 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 27 records from Bäche im Mooswald (Vörstetten). 17 records from Kohlbach (Sulzfeld). 12 records from Ohemoor (Hamburg/Norderstedt). 4 records from Sächsische Schweiz (Wehlener Gebiet). 94 records from Landschaftsschutzgebiet Buchhorst 4. 8 records from Eichendorf Weiher Schwalbach a.Ts.. 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 5 records from Schulinnenhöfe (Gelsenkirchen). 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 1 records from Fledermäuse über der Alster (Hamburg). 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 12 records from Schulgelände Erich-Kästner-Schule. 1 records from Waldtag in und um Seelingstädt. 3 records from Blankenfelder See. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 163 records from Tiere und Pflanzen am Pfannenbach. 1 records from 5. Wiener Gemeindebezirk. 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 401871 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 508 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 1095 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 555 records from FFH-Gebiet "Calwer Heckengäu". 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 15 records from Kühnauer Aue und Kühnauer See. 107 records from BIRDRACE Borussia Zippammer. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 145 records from Gronau - auf der Suche nach dem Neunauge. 73 records from VFD-HH/SH: Pferdweide Lammert. 114 records from Liether Kalkgrube. 116 records from Sürther Aue. 264 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 54 records from Wir erkunden die Hofau, Klasse 5c. 36 records from Liether Park 1 (LMS), Klasse 5b. 177 records from BIRDRACE Mehr Seh Team. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 24110 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 88969 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 15521 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 36254 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 13 records from Tag der Artenvielfalt am Bruckenwasen. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 61 records from Fürstenberger Ralley Teil 3. 52 records from Naturschutzstation Weinberghaus (Dessau). 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 169 records from Expedition "Schulgelände". 1176 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 93 records from Haarbach Höfe. 517 records from Schulzentrum "Parc Hosingen". 146 records from LK 11 im Mönchspark. 74 records from Schulwald Grundschule Brügge. 1424 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 89 records from Schulgelände Paul-Gerhardt-Schule. 80 records from Landschaftsschutzgebiet Schmutterwald. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 371 records from Bannwald Burghauser Forst. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 107 records from Müritz-Nationalpark. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 359 records from Pöhlberg bei Annaberg. 260 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 313 records from BIRDRACE Gätkes Erben. 278 records from BIRDRACE Usedommeln. 144 records from BIRDRACE Die Mohrenlerchen. 272 records from BIRDRACE Niederlausitz-Team. 254 records from BIRDRACE Thüringer Becken-Birders. 65 records from BIRDRACE Federal Birds of Investigation FBI. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 82 records from BIRDRACE Buteo2DO. 91 records from BIRDRACE SchrägeVögel. 96 records from BIRDRACE OAG Neuwerk. 96 records from BIRDRACE Emslandracer. 97 records from BIRDRACE NABUhu Trier!. 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 366 records from Weinberg Reichersdorf. 161 records from BIRDRACE Nord-Seh-Team. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 369 records from BIRDRACE Havelland. 269 records from BIRDRACE Kosmos-Racer. 145 records from BIRDRACE Dith Marsh Sandpiper. 279 records from BIRDRACE Wannacks Topti(c)ker. 287 records from BIRDRACE Pody und Co. 274 records from BIRDRACE Asiola-Quartett. 256 records from BIRDRACE Upupa epöpse. 140 records from BIRDRACE Guckers Offenbach. 157 records from BIRDRACE Rheinische Wasserrallen. 84 records from BIRDRACE Bielefinken. 166 records from BIRDRACE Die Düsselmöwen. 91 records from BIRDRACE NABU LV Hessen. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 138 records from BIRDRACE Arkonauten. 258 records from BIRDRACE Raumpatrouille Oriolus. 69 records from BIRDRACE Pfeifenten. 118 records from BIRDRACE Die Lippegeier. 78 records from BIRDRACE leucorhö statt logorrhö. 80 records from BIRDRACE Falkenberger Fluppis. 82 records from BIRDRACE Die Ziegeneier. 84 records from BIRDRACE Avinauten. 95 records from BIRDRACE BiBi. 95 records from BIRDRACE accipiter hardcore birding. 98 records from BIRDRACE Die Paradiesvögel. 99 records from BIRDRACE TEAM BO-BACHTER. 100 records from BIRDRACE Stuttgart 100 trööt. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 102 records from BIRDRACE Westfälische Nachtigallen. 102 records from BIRDRACE Buteo1DO. 102 records from BIRDRACE Willi goes Birding. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 104 records from BIRDRACE Erlanger Piepmätzchen. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 105 records from BIRDRACE Kiesmätze. 105 records from BIRDRACE coesfelder_vogelkundler. 174 records from BIRDRACE Bon(n)apartemöwen. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 132 records from BIRDRACE Die Wetterauer. 131 records from BIRDRACE Brut. 101 records from BIRDRACE Enger am Spektiv. 158209 records from All Ireland Non-Marine Molluscan Database. 134 records from BIRDRACE Griffin Wood Warblers. 112 records from BIRDRACE Hügelland zu Fuß. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 103 records from BIRDRACE federleser. 103 records from BIRDRACE Die Otzberger. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 106 records from BIRDRACE Ave Goettingen!. 149 records from BIRDRACE Birding Bentheim. 126 records from BIRDRACE Duckehühnchen. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 120 records from BIRDRACE The early birds. 59648 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 119 records from BIRDRACE Tick, Trick und Track. 114 records from BIRDRACE Di-Bi-Di-Birder. 112 records from BIRDRACE Gütersloher Gimpel. 115 records from BIRDRACE Die UHULOGEN. 114 records from BIRDRACE VIE will rock you!. 110 records from BIRDRACE Angeliter Ornis. 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 121 records from BIRDRACE Immerwiederhopf. 108 records from BIRDRACE Diesmal sehen wir mehr. 107 records from BIRDRACE Herford Birders. 173 records from FFH-Gebiet Klosterwasser/Burkau. 66 records from Langes Tannen(LMS), Klasse 5d. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 111 records from BIRDRACE Die Wendehälse. 109 records from BIRDRACE Die Borner. 402 records from Tag der Artenvielfalt in Heidelberg. 2212 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 504 records from Schatzinsel Wangerooge. 144 records from Lustbach-Umland. 62 records from Hettstadt Gehäge. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 113 records from Tornoer Teich. 99 records from Streuobstwiese Stedar. 44 records from Wiesen am Treffpunkt Freizeit. 67 records from Tongrube bei Hettstedt. 121 records from Owere Fiddel. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 61 records from Wälder im Hainbachtal. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 96 records from "Ahrschleife bei Altenahr". 36 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 37 records from Liether Park 2 (LMS), Klasse 6c. 54 records from Königsdorfer Wald. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 54 records from VFD-H: MIttelgebirgsweide. 54 records from Biotope im Schulumfeld. 120 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 62 records from Lebensraum Dorf. 248 records from Schulgarten der Volksschule. 80 records from Feldweg Waldkirchen. 194 records from Bodenteicher Seewiesen. 66 records from Von der Nutzung zur Natur. 49 records from VFD-H.: Rheingau: Bärstadt. 132 records from Aachtobel. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 101 records from Steinbruch Kronungen. 85 records from Ober-Olmer Wald. 85 records from Rund um den Hainbergsee. 214 records from Pflanzen und Tiere im Burgwald. 29 records from Waldwiese. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 61 records from BIRDRACE Baumläufer. 269 records from BIRDRACE Dithmarscher Deichhühner. 84 records from BIRDRACE Birding for Nature. 88 records from BIRDRACE Kingfisher. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 94 records from FFH-Gebiet Paartal. 184 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s.l., Scelioninae). 143 records from BIRDRACE Die Laufenten. 106 records from BIRDRACE Die Schwenker-Birder. 101 records from BIRDRACE nabu-rhein-main.de. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 104 records from BIRDRACE Andechser Stativträger. 277 records from Colección de Entomología - Auchenorrhyncha. 120 records from BIRDRACE Die TUErteltauben. 27 records from Schulgarten Waldorfschule Hassfurt. 47 records from Schulgelände Grolland. 57 records from Schulgarten Janusz-Korczak-Realschule. 69 records from BIRDRACE Mathilden-Käuze. 1965 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 84 records from BIRDRACE Vogelscheuchen. 88 records from BIRDRACE Vogelkucker. 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 837 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 68 records from IBF Monitoring of Orthoptera. 176 records from BIRDRACE Professorenteam. 120 records from BIRDRACE Ornis im Einsatz. 114 records from BIRDRACE LiLaLau. 69 records from Unter hellen Zinnen und finsteren Grotten. 31 records from Düpenauwiesen. 48 records from Wahner Heide LK 12 Biologie. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 99 records from VFD HH/SH "Pferdeweide Lemsahl". 30 records from Geführte Wanderung im Eselsbachtal. 75 records from BIRDRACE Die Kartoffelsäcke. 12844 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 40 records from BUND Naturschutzzentrum St. Julian. 64 records from Rechts des Inn Höhe Hofau Rosenheim. 7685 records from European riparian ground beetles. 17 records from Nachtinsekten am Muldenufer. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 17 records from Bachrenaturierung Littfe. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 52 records from Aktion der Klasse H2 in Simmelsberg. 6325 records from Colección Entomológica de la Universidad de Antioquia. 38 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 152 records from BIRDRACE NAJU-Aspach. 33 records from Schüler erforschen die Helme-Aue. 30 records from Leben auf einer Sturmfläche. 53 records from BIRDRACE Taubenhaucher. 146 records from BIRDRACE VdW Wilder Westen. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 30 records from Riekdahler Wiesen. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 35 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 63-125 µm. 2483 records from NX - Herbário Nova Xavantina. 63 records from Rosarium (LMS), Klasse 6a. 38 records from Was lebt in der Brutzwiese?. 45 records from Reusaer Wald. 12 records from Art´n Vielfalt im Kinderwald. 58 records from Schulgarten Zinnowwald-GS. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 13 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 7 records from Die Bachspezies. 24 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 12 records from Flora und Fauna am Mühlberg. 77 records from VFD-RP: Taunus: Mähweide Dehe. 192 records from "Schwarzwassertal" bei Pobershau. 1 records from Streuobstwiese Alt Necheln. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 2179 records from (Table 7) Absolute abundances of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 61 records from (Table 1) Sedimentology of core D11957P. 5477 records from Colección de mamíferos de la Universidad del Valle. 66 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2137-1. 30 records from Höhle am Neuweg / Sächsische Schweiz. 51 records from Kindervilla Außengelände. 259 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 31 records from Benthic foraminifera counts of sediment core PS2644-2. 88 records from Abundance of benthic foraminifera in late Paleocene to eraly Pliocene sediments of DSDP Hole 74-525A on the Walvis Ridge, South Atlantic (Table 1). 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 59 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >125 µm. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 56 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 541 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 117 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >125 µm. 159 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 566 records from NRM-Herpetology. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, >125 µm fraction. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 63-125 µm. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 63-125 µm. 17 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 30-63 µm. 22 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 192 records from Total living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >30 µm. 123 records from Total living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >30 µm. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, >125 µm fraction. 75 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 250 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 108 records from Total living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >30 µm. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 31 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 76 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 63-125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 421 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, >125 µm fraction. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 85 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 33 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, 63-125 µm fraction. 2833 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 13 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 30-63 µm fraction. 45 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-09. 273 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core GIK17728-1 (Table 4). 545 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1745-5 (Table 8). 128 records from Benthic foraminifera assemblage in sediment core BBLL2_MC4. 145 records from Assemblage of living benthic foraminifera in sediment profile GeoB4909-4. 214 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-43. 114 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-52. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, >125 µm fraction. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 30-63 µm fraction. 50 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 41 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 96 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-51. 10 records from Monitoring of Nigritella nigra in the Kvikne mountains, Tynset, Norway. 349 records from Benthic foraminiferal assemblage in the 125-250 micron fraction of sediment core PS1745-5 (Table 5). 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 663 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 316 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23068-3 in the Norwegian Sea. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 553 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 63-125 µm fraction. 684 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1906-1 (Table 9). 169 records from Benthic foraminifera assemblage in sediment core BBLL2_MC1. 124 records from Benthic foraminifera assemblage in sediment core BBLL3_MC2. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 216 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 2 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 286 records from A revision of Malagasy species of Anochetus Mayr and Odontomachus Latreille (Hymenoptera: Formicidae).. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 412 records from Benthic foraminifera counts of sediment core GIK23063-3. 936 records from Benthic foraminifera counts of sediment core PS1852-1 (GIK21852-1). 212 records from Benthic foraminifera assemblage in sediment core BBLL3_MC1. 48 records from Assemblage of living benthic foraminifera in sediment profile GeoB4901-6. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 335 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 733 records from Distribution of agglutinated foraminifers in sediment core Well 6406/8-1. 333 records from Distribution of calcareous foraminifers in sediment core Well 6407/7-2. 397 records from Benthic foraminifera counts of sediment core GIK23353-5. 530 records from Benthic foraminifera counts of sediment core GIK23352-3. 108 records from Assemblage of living benthic foraminifera in sediment profile GeoB4906-5. 998 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23414-9 in the Norwegian Sea. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 790 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_100MC. 448 records from Benthic foraminifera counts of sediment core GIK23359-2. 874 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_98MC. 172 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 68 records from Abundance of dead benthic foraminifera in sediment core CD86_01_BC1. 129 records from Abundance of living benthic foraminifera in sediment core CD86_01_BC1. 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 68 records from Review of the genus Namadytes Hesse, 1969 (Insecta: Diptera: Mydidae: Syllegomydinae). 5110 records from Live benthic foraminifera in South Atlantic surface sediments. 253 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23256-1 in the Arctic Ocean. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 945 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23414-9 in the Norwegian Sea. 94 records from Distribution of calcareous foraminifers in sediment core Well 6406/8-1. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 329 records from Benthic foraminifera counts of sediment core GIK23351-1. 370 records from Benthic foraminifera counts of sediment core PS1244-2 (GIK23244-2). 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) counts of benthic foraminifera, SE France. 432 records from Benthic foraminifera counts of sediment core PS1246-4 (GIK23246-4). 656 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_107MC. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) benthic foraminifera. 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 549 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 1242 records from Lower Albian Moriez core (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 637 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 3492 records from Species counts of benthic foraminifera of sediment core BOFS5K. 127 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 108159 records from CSIRO, Marine Data Warehouse Biology Records Pre-1998, Australia, 1978-1997. 58 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5. 376 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 358 records from Counting of planktic foraminifera of ODP Hole 182-1129C. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 477 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 289 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 745 records from Counts of the dead benthic foraminifera assemblage in surface sediments of the North Atlantic. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 482 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 3570 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 1550 records from Species counts of benthic foraminifera of sediment core BOFS14K. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 83 records from Abundance of living benthic foraminifera in sediment core CD86_02_BC5. 66 records from Abundance of living benthic foraminifera in sediment core CD86_03_BC4. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 8 records from Aktion des Romain-Rolland-Gymnasiums. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 118 records from Abundance of dead benthic foraminifera in sediment core CD86_03_BC4. 116 records from Abundance of dead benthic foraminifera in sediment core CD86_05_BC5. 38 records from Abundance of dead benthic foraminifera in sediment core CD86_07_BC4. 58 records from Abundance of living benthic foraminifera in sediment core CD86_04_BC4. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 345 records from Diversity of benthic foraminiferal faunas and benthic foraminifera accumulation rates of ODP Site 184-1143. 12 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 2. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction 63-150 µm. 203945 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 31 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction >150 µm. 274 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction >150 µm. 42 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 4 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 30-63 µm fraction. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, >150 µm. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 62 records from Abundance of living benthic foraminifera in sediment core CD86_10_BC4. 21548 records from Benthic foraminifera abundance of ODP Site 184-1143. 1431 records from (Figure 6) Benthic foraminifera counts of sediment core MD01-2378. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 43968 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 141 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction >150 µm. 57 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction 63-150 µm. 2210 records from Merseyside BioBank - North Merseyside Mammals (unverified). 313 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction >150 µm. 25 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 17 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, >150 µm. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 101 records from (Table 4a) Downcore distribution of live benthic foraminifera of sediment core SW_3a, California continental borderland. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 75 records from Faunal assemblage of sediment core GS7603-9. 79 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction >150 µm. 144 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction 63-150 µm. 77 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 25 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 13 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 30-63 µm fraction. 1100 records from (Fig. 6) Assemblage of benthic foraminifera in sediment core GeoB6730-1. 5 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, >125 µm fraction. 49 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 7 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 30-63 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 11 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, >150 µm. 23 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, 63-150 µm. 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 66 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, 63-150 µm. 24 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, 63-150 µm. 41 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC469. 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 516 records from (Appendix B1) Calcareous nannofossils of ODP Site 208-1262. 267 records from Assemblage of living benthic foraminifera in sediment core GeoB3713-1. 89 records from Assemblage of living benthic foraminifera in sediment core GeoB4918-4. 73 records from Faunal assemblage of sediment core GS7603-13. 95 records from Total foraminifera counts from multinet M31/2_MSN896. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 55 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 63-125 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 18 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, >150 µm. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 69 records from (Table T6) Calcareous nannofossil stratigraphy of ODP Hole 198-1210A. 13737 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, 63-150 µm. 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, 63-150 µm. 63 records from Plasm bearing foraminifera counts of multinet SO117_MSN1245. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, >150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 67 records from Number of live benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 569 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 248 records from Counts of Quaternary foraminifera of sediment core CRP-1 (App. 1). 141 records from Assemblage of living benthic foraminifera in sediment core GeoB3702-2. 76 records from Faunal assemblage of sediment core GS7603-10. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 69 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 65 records from (Table 4b) Downcore distribution of live benthic foraminifera of sediment core SW_3b, California continental borderland. 140 records from Assemblage of living benthic foraminifera in sediment core GeoB1720-3. 120 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 129 records from Assemblage of living benthic foraminifera in sediment core GeoB3705-2. 190 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB3708-1. 131 records from Assemblage of living benthic foraminifera in sediment core GeoB3715-1. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB4912-4. 588 records from (Table 5) Foraminiferal numbers of empty test of important species in surface sediments. 148 records from Faunal assemblage of sediment core GS7603-11. 23 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, 63-150 µm. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 134 records from Number of dead benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 28 records from Counts of recycled Pliocene foraminifera of sediment core CRP-1 (App. 1). 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 109 records from Assemblage of living benthic foraminifera in sediment core GeoB3703-4. 207 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 320 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 166 records from Assemblage of living benthic foraminifera in sediment core GeoB3725-1. 142 records from Assemblage of living benthic foraminifera in sediment core GeoB4904-7. 119 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 347 records from (Table 4) Standing stock values of important species in surface sediments. 77 records from Faunal assemblage of sediment core GS7603-12. 75 records from Faunal assemblage of sediment core TR149-32. 152 records from Faunal assemblage of sediment core TR149-38b. 5438 records from (Appendix A) Benthic foraminiferal assemblages in sediments of the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 361 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 90-590B in the southwestern Pacific. 2381 records from Hawaiian Algal Database. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 364 records from Dornwanger Moos. 70 records from Faunal assemblage of sediment core GS7603-14. 76 records from Faunal assemblage of sediment core GS7603-8. 181 records from Occurence of monothalamous foraminifera in Admiralty Bay, King George Island, West Antarctica (Table 1, 2). 915 records from (Appendix Table 2) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 14 records from Abundance of Globorotalia menardii of sediment core GeoB2110-3. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 239 records from Planktic foraminifera counts at CTD station M39/4_352CTD-11. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 131 records from Total foraminifera counts from multinet M31/2_MSN887. 72 records from Faunal assemblage of sediment core TR149-35. 76 records from Faunal assemblage of sediment core TR149-37. 891 records from Benthic foraminifera accumulation rate of sediment core MD01-2378 during marine isotope stage 3. 734 records from Stable oxygen isotope ratios of foraminifera from late middle Eocene sediments of ODP Site 171-1052 from Blake Plateau, West Atlantic Ocean (Appendix). 359 records from (Appendix A) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene desiments of DSDP Hole 94-607 from the North Atlantic. 671 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 66 records from (Table 2) Distribution of calcareous benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 1023 records from (Appendix Table 1) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean. 1100 records from (Table AT3) Planktonic foraminiferal strati
Keywords: GBIF; biodiversity; species occurrences